Concept BUSINESSMEN in lingual networks (on the material of the English language) - Старцева, Наталія Миколаївна; Сапрун, Ірина Рустамівна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2018)
The article is devoted to the cognitive-linguistic research of one of the basic concepts of the business sphere – the concept BUSINESSMAN, using the nominative corpus of the English language, vocabulary definitions of the lexeme businessman, the ideas and views of the members of the English language society about the businessman and the representation of the concept in modern discourse. Cognitive features of the concept BUSINESSMAN, its ontological links are structured according to the methodology of lingual networks in the form of five basic frames – the Thing, Action, Possession, Identification, and Comparison frames. Identified on a propositional basis, these frames and their varieties form the frame (cognitive) network of the given concept.